(untitled) (GIST – Education and Learning Research Journal, 2019)
This article contains a description of a research project carried out with a group of English Language Pre-service Teachers (ELPTs) of a state University in Bogotá, Colombia. The purpose of the study was to portray the experiences the ELPTs went through as English language learners, their feelings and insights as such. The main source to collect data was the autobiographies. The results show that the English language learners’ process of learning has a strong influence of the language policies connected to the National Program of Bilingualism. They also show that it is necessary to create a cumulative program of English for each phase of schooling in order to avoid overlapping and to provide a more motivating learning process.